Hypothetical role of hypoxia-inducible factor-1 in adaptations to microgravity - Sook Chun, Yang; Hargens, Alan R. (Revista Cubana de Investigaciones Biomédicas, 2019)
Maintaining health in microgravity and overcoming environmental hazards such as cosmic radiation are essential for long-term space flight. Recent studies have focused on the involvement of hypoxia-inducible factor (HIF)-1 in altered gravity using cell-based or in vivo mouse model systems. HIF-1alpha and its target downstream gene expression are differentially expressed in hypergravity and microgravity. Nevertheless, underlying molecular mechanism of HIF-1alpha involvement is still unclear. Herein, we analyzed the 2019 Science paper by Garrett-Bakelman and coauthors in which NASA performed multidimensional analyses of long-term human spaceflight in identical twin astronauts. Correlations were found between the expression of HIF-1alpha related cytokines and prolonged space flight. We hypothesize that HIF-1alpha is a molecular target for the development of therapeutics to prevent the detrimental effects of microgravity and cosmic radiation on astronauts during long-term space flight.